Defective Slc7a7 transport reduces erythropoietin compromising erythropoiesis - Judith Giroud-Gerbetant; Fernando Sotillo; Gonzalo Hernández; Irene Ruano; David Sebastián; Joana Fort; Mayka Sánchez; Günter Weiss; Neus Prats; Antonio Zorzano; Manuel Palacín; Susanna Bodoy (Molecular Medicine)
Abstract Background Lysinuric protein intolerance is a rare autosomal disorder caused by mutations in the Slc7a7 gene that lead to impaired transport of neutral and basic amino acids. The gold standard treatment for lysinuric protein intolerance involves a low-protein diet and citrulline supplementation. While this approach partially improves cationic amino acid plasma levels and alleviates some symptoms, long-term treatment is suggested to be detrimental and may lead to life-threatening complications characterized by a wide range of hematological and immunological abnormalities. The specific cause of these hematopoietic defects—whether intrinsic to hematopoietic cells or driven by external factors—remains unclear. Given the limitations of current citrulline-based treatments and the unknown role of SLC7A7 in red blood cell production, there is an urgent need to investigate the pathways affected by SLC7A7 deficiency. Methods We employed total inducible and cell type-specific Slc7a7 knockout mouse models to determine whether the hematological abnormalities observed in LPI are due to the loss of Slc7a7 function in hematopoietic cells. We analyzed erythropoiesis in these mice and performed bone marrow transplantation experiments to assess the role of Slc7a7 in erythroblasts and myeloid cells. The statistical significance of differences between groups was evaluated via standard statistical tests, including Student’s t test and ANOVA. Results Whole-body Slc7a7 knockout mice presented impaired erythropoiesis. However, this defect was not replicated in mice with Slc7a7 deficiency restricted to erythroblasts or myeloid cells, suggesting that the observed hematopoietic abnormalities are not due to intrinsic Slc7a7 loss in these cell types. Additionally, bone marrow transplants from control mice did not rescue the hematopoietic defects in Slc7a7-deficient mice, nor did the transplantation of Slc7a7-deficient cells induce defects in control recipients. Further investigation indicated that defective erythropoiesis is linked to impaired erythropoietin production in the kidney and subsequent iron overload. Conclusions The hematopoietic defects in the Lysinuric protein intolerance mouse model are not caused by intrinsic Slc7a7 loss in hematopoietic cells but rather by impaired erythropoietin production in the kidney. This finding opens potential avenues for therapeutic strategies targeting erythropoietin production to address hematological abnormalities in humans with lysinuric protein intolerance.